Smoking and periodontal tissues: a review - João Batista César Neto; Ecinele Francisca Rosa; Cláudio Mendes Pannuti; Giuseppe Alexandre Romito (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The impact of smoking on general health has been widely studied and is directly related to several important medical problems including cancer, low birth weight, and pulmonary and cardiovascular disease. In the past 25 years, there has also been an increasing awareness of the role of cigarette consumption in oral health problems such as periodontal disease. Smoking is considered the major risk factor in the prevalence, extent and severity of periodontal diseases. This article will discuss the available evidence and provide the reader with an overview of the impact of smoking and its cessation on the pathogenesis and treatment of periodontal diseases.